A new species of the genus Oligodon Fitzinger, 1826 (Squamata: Colubridae) from coastal southern Vietnam - Vassilieva, Anna B. (Zootaxa, 2015)
A new species of the genus Oligodon from the coastal area of Binh Chau–Phuoc Buu Nature Reserve, Ba Ria–Vung Tau Province, southern Vietnam, is described. Oligodon arenarius sp. nov. is distinguishable from all other species by the unique combination of the following characters: medium size; 17 dorsal scale rows; 6–8 maxillary teeth, the posterior three being enlarged; head scalation lacking a loreal but usually including a presubocular; divided nasal; two postoculars; 131–144 ventrals; 36–60 subcaudals; unforked hemipenis, without spines or obvious papillae; sexual dimorphism displayed in the number of subcaudals (36–40 in females, 58–60 in males) and a relative tail length, tails being quite long in males (TaL/TL = 0.26–0.28) and moderate in females (TaL/TL = 0.13–0.17); head coloration pattern including ocular band, temporal bands and chevron-shaped mark on nape; dorsal coloration without distinct pattern, uniform or with dark speckling; ventrals pinkish in life, immaculate. To date, this species appear to be endemic to Vietnam.